Terapi kognitif pada permasalahan hubungan sosial - Lintang Aulia Utami (Universitas Muhammadiyah Malang, 2021)
One of the tasks of child development is to establish and build social relationships with friends and their environment. Individuals who have been socially excluded will withdraw by not having relationships with others because of the fear of the negative evaluation feom others. The assessment methods used were interview, observation and psychological tests namely were graphic tests, and the Intelligenz Structure Test (IST). The intervention used to change the subject's negative thoughts to become more positive is cognitive therapy. The cognitive therapy process that was given as many as 6 sessions with the target subject was able to change his negative thoughts into more positive ones. The results of the intervention show that the subject was able to replaces his negative thoughts with positive thoughts which ultimately makes the subject feel no guilt anymore.